Water Absorption And Mechanical Properties Evaluation Of Surface Modified Abs Printing Parts - Leite, Marco (2016)
The aim of this paper was to investigate the effect of a sealing protective treatment on the water absorption and mechanical properties of acrylonitrile butadiene styrene (ABS) printed parts by fused deposition modelling (FDM). Protective products include aqueous acetone solutions with different concentrations, a polyurethane based varnish and another varnish aqueous acrylic based. The open porosity was estimated by the absorption coefficient and the total amount of water retained obtained from water absorption tests. The mechanical characterization was performed by compressive and tensile tests. Different specimens with different build directions and raster angles were used. Treatment with an acrylic based varnish was found to both preserve the structure fidelity of the samples, to reduce the open porosity, and to maintain the compression and tension properties of the samples in different build directions and raster angles.